2022
DOI: 10.1111/aos.15264
|View full text |Cite
|
Sign up to set email alerts
|

Presence and development of diabetic retinopathy in 153 238 patients with type 2 diabetes in the Danish Registry of Diabetic Retinopathy

Abstract: Purpose The purpose of the study was to evaluate the prevalence and incidence of diabetic retinopathy (DR) along with associated markers in patients with type 2 diabetes in the Danish DR‐screening programme. Methods We included all persons with type 2 diabetes in the Danish Registry of Diabetic Retinopathy, who had attended at least one episode of DR screening in 2013–2018. DR was classified as levels 0–4 indicating increasing severity. Data were linked with various national health registries to retrieve infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 30 publications
(25 reference statements)
0
6
2
Order By: Relevance
“…In contrast, a recent nationwide registry-based study from Denmark with a similar cohort size, n = 153 238, median age 60 years, reported a prevalence rate of 8.8%. The shorter duration of diabetes in the Danish cohort may have contributed to the lower prevalence compared to our study (Grauslund et al, 2023). Data from populationbased studies report slightly lower DR prevalence rates than the present study.…”
Section: Discussioncontrasting
confidence: 81%
“…In contrast, a recent nationwide registry-based study from Denmark with a similar cohort size, n = 153 238, median age 60 years, reported a prevalence rate of 8.8%. The shorter duration of diabetes in the Danish cohort may have contributed to the lower prevalence compared to our study (Grauslund et al, 2023). Data from populationbased studies report slightly lower DR prevalence rates than the present study.…”
Section: Discussioncontrasting
confidence: 81%
“…Previous studies disagree on the role of pre-surgical HbA1c levels in regards to DR progression; with one study showing that a higher baseline HbA1c with a significant post-surgical drop increased the risk of DR progression [ 17 ], another study did not find an association [ 18 ]. The rates of DR worsening were also lower than seen amongst the general screening population of patients with type 2 diabetes in the Danish screening program [ 19 ] suggesting that patients eligible for bariatric surgery are following the pre-surgical guidelines promoting good pre-surgical glycemic stability, weightloss and lifestyle changes, amongst other initiatives, all intended to ensure optimal results of surgery [ 20 ]. Another reason for good glycemic stability, and generally acceptable biochemical measurements amongst our population as a whole, might be the effectiveness of the screening program itself alongside other healthcare appointments at the patients primary care physician; discovering tendencies towards worsening in DR or irregularities in systemic examinations and bloodwork, thus being able to induct initiatives to improve glycemic stability, and in turn halt further progression.…”
Section: Discussionmentioning
confidence: 99%
“…We identified 11 population-based studies that investigated the incidence of PDR over various follow-up periods of four [8,[16][17][18], five [11,[19][20][21][22], nine [23], ten [10] and 25 years [24]. Among these studies, three focused on patients with type 1 diabetes [8,10,24], five on patients with type 2 diabetes [11,16,18,20,23], while four studies encompassed populations that comprised patients with both type 1 and 2 diabetes [17,19,21,22]. The incidences of PDR are displayed in Fig.…”
Section: Incidence Of Pdrmentioning
confidence: 99%
“…A Danish cohort study of patients with type 2 diabetes who attended the Danish screening program for DR showed a 5 year incidence of 3.8% for DR [ 11 ] compared to 4% in a study from United Kingdom (UK) [ 12 ]. A group from India reported a 4 year incidence of 9.2% [ 13 ], while studies of older date from Hong Kong [ 14 ], Australia [ 15 ] and USA [ 16 ] reported substantially higher 5 year incidences of 15.2, 22.2 and 38.6%, respectively.…”
Section: Global Epidemiology Of Drmentioning
confidence: 99%